عزل و تشخيص مركب الفايسين من نبات عباد الشمس - دهري نعمهجبار (University of Thi-Qar Journal of Science, 2019)
The present study is included isolation & identification of vicine which backed to phenolic glycosides from H.annus L. seeds . The extracted vicine is compared with standard vicine. After isolation this compound some qualitative test have been carried out, These test showed that isolated compound is from phenolic glycosides. The isolated compound it showed one spot in T.L.C . It is also identified by melting point and UV and IR spectra. The results of all above were showed similarity between both isolated compound and standard vicine